The role of women in small business development in Uzbekistan - Джамалова , Жамила (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
The report examines the importance of women in the development of the Uzbek economy, specifically analyzing their activities in small and medium-sized businesses, providing examples of successful women's entrepreneurial projects, and listing various barriers to successful women's business activities in Uzbekistan. In modern Uzbekistan, increasing attention is being paid to the role of women in entrepreneurship. Small business is becoming an important avenue for economic growth, job creation, and improved family well-being. Women are one of the driving forces in these processes.